Report on the Clare Committee Proposal for Rules of Admission to the Federal District Courts in the Second Circuit. Report of Special Committee on Admissions to the Bar - Association of American Law Schools, Washington, DC.; Association of American Law Schools, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
The Clare Committee recommends that admission to practice in the federal district courts in the Second Circuit be limited to those who have studied five subjects, including trial advocacy, in law school or after graduation in approved continuing legal education programs. The practical effect of adoption of these recommendations would be to require the law schools to offer and the students to take the required subjects. The committee's recommendations reflect the opinion that there is a need for improvement in the level of performance of trial advocates. The Association of American Law Schools' report on the recommendations reviews the proposal and its factual premises, and summarizes and examines the alternative requirements for admission to practice in a federal district court. (JMF)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Admission Criteria; Court Litigation; Curriculum; Curriculum Development; Curriculum Evaluation; Higher Education; Law Schools; Lawyers; Legal Education; Legal Responsibility; Professional Education; Clare Committee; Association of American Law Schools; Books